Definition of inferred faults using 3D geological modeling techniques: A case study in Tympaki Basin in Crete, Greece - Panagopoulos, G.; Giannakakos, E.; Manoutsoglou, E.; Steiakakis, E.; Soupios, P.; Vafidis, A. (Bulletin of the Geological Society of Greece, 2013)
The purpose of this paper is to recognize inferred faults in Tympaki basin (Crete island) which cannot be observed on the surface, as the area is covered by recent deposits. The identification of the faults is crucial for the study of the sea-water intrusion in Tympaki basin that has been observed during the last years. 3D geological modelling techniques were used for reaching the aforementioned goal. The data used include the digital elevation model (DEM) of the area, the boundary surface between geologic formations and the litho - stratigraphic logs of thirty nine (39) wells. Initially a 3D stratigraphic model was set-up depicting the spatial extension of Plio-Quaternary and Neogene deposits. Next, with emphasis on the litho - stratigraphic logs of the wells, the boundary between the geological formations was defined in a 3D space. The regional unconformity between the Plio-Quaternary and Neogene formations is possibly the result of tectonic activity of inferred faults. The traces of the inferred faults were drawn and they were compared with the faults suggested by previous studies.